YIELD AND YIELD ATTRIBUTES OF Bt COTTON AS INFLUENCED BY DIFFERENT DRIP FERTIGATION SCHEDULES - G. R.CHARY, JARAPATI CHANDRA SHEKAR, K. AVIL KUMAR and (The Journal of Research, PJTSAU, 2019)
Cotton (Gossypium spp.) popularly known as â€œwhite goldâ€, is an important commercial fibre crop which plays an important role in livelihood of around 250 million people globally and it accounts for 75 per cent of the fibre used in the textile industry in India. India is the largest cotton growing country in the world with an area of 119.27 lakh ha. The area of cotton in Telangana is 18.13 lakh ha with productivity of 423 kg lint ha-1 which is lower compared to national average productivity of 487 kg lint ha-1 (DoES, 2015). Water and fertilizers are important critical input factors for cotton production. The lower yields of cotton could be attributed to inefficient irrigation and fertilizer management practices (Veeraputhiran and Chinnusamy, 2009). Drip fertigation, therefore, is the new approach for water and nutrient management as the nutrients and water are applied directly into the soil, where the roots are actively growing and found to increase the efficiency of fertilizer use. Hence, the experiment was planned to study the nitrogen and potassium fertigation schedules on yield and yield attributes of Bt cotton under different fertigation schedules and irrigation regimes.